2020
DOI: 10.1101/2020.02.29.20029439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ddPCR: a more sensitive and accurate tool for SARS-CoV-2 detection in low viral load specimens

Abstract: 32Background: Real-Time PCR (RT-PCR) is widely used as the gold standard for 33 clinical detection of SARS-CoV-2. However, due to the low viral load in patient 34 throat and the limitation of RT-PCR, significant numbers of false negative reports are 35 inevitable, which should not be ignored. 36 Methods: We explored the feasibility of droplet digital PCR (ddPCR) to detect 37 SARS-CoV-2 from 57 clinical pharyngeal swab samples and compared with RT-PCR 38 in terms of the sensitivity and accuracy. Among 57 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 16 publications
2
65
0
1
Order By: Relevance
“…First strand cDNA was synthesized using PrimeScript RT kit (TakaRa). Optimized ddPCR was used to detect the presence of SARS-CoV-2 viruses following our previous study 10 . Analysis of the ddPCR data was performed with QuantaSoft software (Bio-Rad).…”
Section: Analytical Methods and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…First strand cDNA was synthesized using PrimeScript RT kit (TakaRa). Optimized ddPCR was used to detect the presence of SARS-CoV-2 viruses following our previous study 10 . Analysis of the ddPCR data was performed with QuantaSoft software (Bio-Rad).…”
Section: Analytical Methods and Data Analysismentioning
confidence: 99%
“…In this study, we sampled airborne SARS-CoV-2 and its aerosol deposition at 30 sites in two designated hospitals and public areas in Wuhan and then quantified the SARS-CoV-2 copy counts of aerosol samples using a robust droplet digital PCR-based detection method (ddPCR) 10 . The two hospitals are exclusively used for COVID-19 patient treatment during the outbreak but each with unique characteristics serving different purposes.…”
mentioning
confidence: 99%
“…Lu et al report 96.3% accuracy for testing of clinical samples using digital PCR and were able to detect virus in 4 patient samples that were deemed negative by RT-PCR (Lu et al 2020a). Furthermore, digital droplet methods have been shown to be capable of detecting down to 0.4 viral RNA copies/µL in patient samples (Suo et al 2020). Because digital PCR allows for more careful quantitation of viral RNA copy number over the course of the disease, this highly sensitive test may also be useful to evaluate treatment progress or assess patient release after quarantine.…”
Section: Other Nats ("Thinking Outside the Box")mentioning
confidence: 99%
“…In this context, the droplet digital PCR (ddPCR) might be more appropriate for quantitation of viral loads as reported previously 7 . The ddPCR allows precise quantitation of nucleic acid copies without the need of any calibration curve and with higher resistance to the ampli cation inhibitors compared to the quantitative real-time PCR 8 , and some recent studies reported the usage of ddPCR for the quantitation of SARS-CoV-2 [9][10][11][12][13] . However, all these ddPCR procedures included the RNA extraction/puri cation step leading to potential errors for the ampli cation due to variable and suboptimal nucleic acid yields 14,15 .…”
Section: Introductionmentioning
confidence: 99%